2014
DOI: 10.4161/23723548.2014.961825
|View full text |Cite
|
Sign up to set email alerts
|

Cell survival is dicey without Dicer

Abstract: The cellular requirements of Dicer, an essential miRNA processing enzyme, and the consequences of altered levels of it on tumorigenesis are incompletely understood. We review the effects of Dicer loss in cells of different origin and whether loss of p53 permits cell survival and growth in the absence of Dicer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…All of the donors were first clinically assessed by professionals for PTSD. Participants were evaluated by the psychometric properties of the PTSD Checklist (PCL) 50 and the PTSD diagnosis was validated by the Clinician Administered PTSD Scale 51 and the Diagnostic and Statistical Manual of Mental Disorder (DSM-V) 4 . (Demographics of the PTSD patients included for the microarray and RNA-Seq analyses is provided in Table 1 ).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the donors were first clinically assessed by professionals for PTSD. Participants were evaluated by the psychometric properties of the PTSD Checklist (PCL) 50 and the PTSD diagnosis was validated by the Clinician Administered PTSD Scale 51 and the Diagnostic and Statistical Manual of Mental Disorder (DSM-V) 4 . (Demographics of the PTSD patients included for the microarray and RNA-Seq analyses is provided in Table 1 ).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The values indicate mean and the values in parentheses for age, depression, anxiety and PTSD score indicates standard deviation. Depression, anxiety and PTSD scores were determined as per PCL, CAPS and DSM criteria 4 50 51 . * African American; **Caucasian; ***Hispanic.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Prior to studies on the specific miRNAs, we first asked if miRNAs are involved in cycling quiescence of TMZ resistant GBM cells. This was addressed by knockdown of Dicer, which is a type III RNase and a key enzyme in the maturation of miRNAs (Adams and Eischen, 2014; van den Beucken et al, 2014). We established resistant GBM cells in which Dicer 1 was knocked down, as previously described (Munoz et al, 2014a).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, deficiency in DCR1, the enzyme responsible for the generation of mature miRNA by cleaving pre-miRNA to ~22 nucleotide mature miRNAs, is known to result in deficient miRNA biogenesis and can lead to lowered abundance of mature miRNAs. 14 , 15 , 16 Remarkably, a recent report showed that the expression of Dicer1 was decreased in PTSD, and this was linked to the lowered expression of miR-3130-5p. 17 Interestingly, the authors reported only miR-3130-5p as significantly downregulated but did not show any link between the downregulated miRNA and any physiological changes in PTSD.…”
Section: Introductionmentioning
confidence: 99%